Crystal structure and characterization of new cadmium complex from 4-pyridin-carbohydrazide and 2-chlorobenzaldehyde - Hashemian, Saeedeh; Mangeli, Mahbobah (European Journal of Chemistry, 2017)
Reaction of 4-pyridincarbohydrazide, 2-chlorobenzaldehyde and Cd(II) ion in ethanol resulted the complex trans-[Cd(H2O)4(C13H10N3ClO)2](NO3)2. The title complex was characte-rized by elemental analyses, UV-Vis and IR spectroscopy. The structure of complex also was established by single crystal X-ray diffraction analysis. The [Cd(H2O)4(C13H10N3ClO)2](NO3)2complex has monomeric structure with monoclinic crystal system and space group of P21/n, a = 7.7720(16) Å, b = 17.594(4) Å, c = 11.823(2) Å, β = 97.29(3)° with Z = 2. The cadmium atom in the crystal structure has octahedral geometry by coordination of the two nitrogen atoms of ligand and four oxygen atoms of water molecules.